2018
DOI: 10.1021/acs.jpcc.8b00774
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Boron Nitride Nanotubes with Aluminum: A Computational Study

Abstract: The interaction of boron nitride nanotubes (BNNTs) with Al has been investigated by means of quantum chemical calculations. Two model structures were used: a BNNT adsorbing a four atom Al 4 cluster and a BNNT adsorbed on Al surfaces of different crystallographic orientations. The BNNTs were modeled as (i) pristine and as (ii) having a boron (B-) or a nitrogen (N-) vacancy defect. The results indicated that the trends in binding energy for Al 4 clusters were similar to those of the adsorption on Al surfaces, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In the computational research made by Rohmann et al [21], it has been reported that the tensile strength value of BNNT reinforced aluminum matrix composite produced by powder metallurgy can only reach 300 MPa with the addition of 3 to 5 wt% powder [17]. Ultimate tensile test results (Fig 7) are varying between 250-350 MPa.…”
Section: Resultsmentioning
confidence: 92%
“…In the computational research made by Rohmann et al [21], it has been reported that the tensile strength value of BNNT reinforced aluminum matrix composite produced by powder metallurgy can only reach 300 MPa with the addition of 3 to 5 wt% powder [17]. Ultimate tensile test results (Fig 7) are varying between 250-350 MPa.…”
Section: Resultsmentioning
confidence: 92%
“…In addition, it was noted that the BNNTs breaks and slide inside the aluminum matrix. Rohman et al, 12 investigated the interaction of BNNTs with aluminum using quantum chemical calculations. They have taken neat BNNTs and BNNTs with vacancy defects of boron and nitrogen atoms interaction with Al 4 cluster and Al surface.…”
Section: Theoretical Studies On Bnnts Filled Mmncsmentioning
confidence: 99%
“…A significant drawback in the addition of CNTs to metallic matrices is their low-temperature stability (~500 o C), and high reactivity with metal matrices resulting in the partial or complete transformation to brittle carbide species. 55,56 . Improved wetting conditions between the metal matrix and the nanotube was found to impart increments in elastic modulus of the Al matrix by 2× (134 GPa), with effective transfer of load mechanisms such as crack bridging, nanotube pull-out, etc 4,[53][54][55] ( Figure 10 b and c).…”
Section: Interfacial Interactions Between Bnnt and Metalmentioning
confidence: 99%